(untitled) (Journal of the Asiatic Society of Bangladesh, Science, 2015)
The seeds of Dendrobium lindleyi were germinated on 0.8% (w/v) agar solidified Murashige and Skoog (MS) as well as Phytamax (PM) basal media. The germination rate was found to be better on PM medium. The germinated seedlings underwent rapid elongation on Plant Growth Regulators (PGRs) supplemented media and the highest growth was recorded on MS with 3% (w/v) sucrose + 2.0 mg/1 6-Benzyl Amino Purine (BAP) + 0.1mg/1 Indole-3-Butyric Acid (IBA). The seed derived seedlings developed strong and stout roots on half strength MS medium with 1.5% sucrose. For micropropagation the pseudobulb segments were used as explant and the lower part of pseudobulb segment produced highest number of multiple shoot buds (9-10/segment) on agar solidified MS medium supplemented with 3% (w/v) sucrose + 2.5 mg/1BAP + 0.1% (w/v) Activated Charcoal. The highest rate of elongation and rooting was found from multiple shoot bud derived seedlings as well as same seed derived seedlings. Seed and multiple shoot bud derived rooted seedlings were finally transferred to outside natural environment by successive phases of acclimatization. Asiat. Soc. Bangladesh, Sci. 41(2): 163-171, December 2015